The role of decompressive craniectomy in the context of severe traumatic brain injury: summary of results and analysis of the confidence level of conclusions from systematic reviews and meta-analyses. (2019)
Introduction: Traumatic brain injury (TBI) is a global epidemic. The incidence of TBI in low and middle-income countries (LMICs) is three times greater than in high-income countries (HICs). Decompressive craniectomy (DC) is a surgical procedure to reduce intracranial pressure (ICP) and prevent secondary injury. Multiple comparative studies, and several randomized controlled trials (RCTs) have been conducted to investigate the influence of DC for patients with severe TBI on outcomes such as mortality, ICP, neurological outcomes, and intensive care unit (ICU) and hospital length of stay. The results of these studies are inconsistent. Systematic reviews and meta-analyses have been conducted in an effort to aggregate the data from the individual studies, and perhaps derive reliable conclusions. The purpose of this project was to conduct a review of the reviews about the effectiveness of DC to improve outcomes. Methods: We conducted a systematic search of the literature to identify reviews and meta-analyses that met our pre-determined criteria. We used the AMSTAR 2 instrument to assess the quality of each of the included reviews, and determine the level of confidence. Results: Of 973 citations from the original search, five publications were included in our review. Four of them included meta-analyses. For mortality, three reviews found a positive effect of DC compared to medical management and two found no significant difference between groups. The four reviews that measured neurological outcome found no benefit of DC. The two reviews that assessed ICP both found DC to be beneficial in reducing ICP. DC demonstrated a significant reduction in ICU length of stay in the one study that measured it, and a significant reduction in hospital length of stay in the two studies that measured it. According to the AMSTAR 2 criteria, the five reviews ranged in levels of confidence from low to critically low. Conclusion: Systematic reviews and meta-analyses are important approaches for aggregating information from multiple studies. Clinicians rely of these methods for concise interpretation of scientific literature. Standards for quality of systematic reviews and meta-analyses have been established to support the quality of the reviews being produced. In the case of DC, more attention must be paid to quality standards, in the generation of both individual studies and reviews.